Coming of age in medieval Egypt: female adolescence, Jewish law, and ordinary culture - Krakowski, Eve (Princeton University Press, 2018)
Cover -- Title -- Copyright -- CONTENTS -- List of Illustrations -- Acknowledgments -- Technical Notes -- Abbreviations -- INTRODUCTION -- PART I WOMEN IN A PATRONAGE CULTURE -- CHAPTER 1 The Family -- CHAPTER 2 The Courts and the Law -- PART II UNMARRIED DAUGHTERS -- CHAPTER 3 A Ripened Fig: Age at First Marriage -- CHAPTER 4 The Economics of Female Adolescence -- CHAPTER 5 A Virgin in Her Father's House: Modesty, Mobility, and Social Control -- PART III BECOMING A WIFE -- CHAPTER 6 Marriage Choices -- CHAPTER 7 Defining Marriage: Legal Agreements and Their Uses -- CHAPTER 8 In the Marital Household -- CONCLUSION -- Bibliography -- Index of Geniza Documents Cited -- Index of Jewish and Islamic Texts Cited -- General Index.